Otomycosis treatment: Topical Drops versus Cream - A prospective randomized study - Prasun Mishra; Sheenu Sachdeva; Maitri Kaushik; Deeksha Agrawal (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Introduction: Otomycosis, is one of the most common conditions encountered in a ENT practice. Difference of opinion does exist regarding ideal treatment modality.  Aim: Compare the treatment effi cacy of 1% Clotrimazole drops with 1% Clotrimazole Cream in management of otomycosis.  Method: Randomized control study was performed over 3 months. 60 patients, clinically diagnosed with otomycosis were included in study. Patients were randomly allotted to treatment arms of either 1% clotirmazole drops or 1% clotirimazole cream. Improvement in symptoms of pain, pruritis and blocked sensation on one and two weeks follow up was recorded. External auditory canal was evaluated for improvement in otomycotic debris. All patients were asked the opinion about preferred modality of treatment.  Results: When compared to the symptoms on day one at day 07, the change in symptoms in both the groups was signifi cant (p<0.05). Significant difference was also noted for the improvement in otomycotic debris in both the groups. The group with cream had significantly more blocked sensation. On second week follow up, significant improvement was noted for all the symptoms and otomycotic debris. 45 out of 60 patients preferred using cream.  Conclusion: 1% topical clotrimazole and cream are equally effective in management of otomycosis